Development of Single-Walled Carbon Nanotube-Based Biosensor for the Detection of Staphylococcus aureus - Hyun-Kyung Choi; Jinyoung Lee; Mi-Kyung Park; Jun-Hyun Oh (Journal of Food Quality)
The goal of this research is to develop a single-walled carbon nanotube- (SWCNT-) based biosensor to detect Staphylococcus aureus. The specificity of 11 bacteria and polyclonal anti-Staphylococcus aureus antibodies (pAbs) was determined using an indirect ELISA. The pAbs were immobilized onto sensor platform after the hybridization of 1-pyrenebutanoic acid succinimidyl ester (PBASE). The resistance difference (ΔR) was calculated using a potentiostat. The bacteria detected by the biosensor were observed using a scanning electron microscope (SEM). The optimum concentration of SWCNTs on the platform was determined to be 0.1 mg/mL. The binding of pAbs with S. aureus resulted in a significant increase in resistance value of the biosensor (P<0.05). The SEM images confirmed the specific binding of S. aureus on the biosensor. The SWCNT-based biosensor was able to detect S. aureus with a limit of detection (LOD) of 4 log⁡CFU/mL.